Durabilitas Resistensi Varietas Unggul Jagung Terhadap Penyakit Bulai dari Spesies Peronosclerospora Maydis - Pakki, Syahrir (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
The research of the durability of maize high-yielding variety resistance towards downy meldew from the Peronosclerospora maydis species aims to discover the durability of maize high-yielding variety resistance towards Downy mildew P. maydis. This research was conducted in Kediri, East Java particularly in downy mildew endemic area, from pathogen which causes P. maydis. There are 10 new high-yielding varieties that were tested. The experiment was compiled in group plan with 3 rehearsals. Every patch size are 5 x 4, the plant space is 75 x 20 cm, the population each patch is 90 plants. At the age of 10 days after the cultivation, the plants were supplied with mixed basic fertilizer from urea, ZA, SP-36, and KCI in which their amount are 100 kg, 100 kg, and 100 kg/ha. At the second and third fertilization on the 30th and 45th days after the cultivation, the plants were supplied 100 kg urea/ha each fertilization period. The result show that the variety of Bima 5, HJ 21 Agritan, Bima-14 Batara dan Bisi 19 URI which previously had a high characteristic of resistance towards downy mildew performed low resistance durability or turned to be vulnerable with downy meldew infection approximately 62 % - 77,25 %. In contrast, the variety of Bima-3 Bantimurung, Bima -20 URI, Bima 15 Sayang and Lagaligo composite maize indicated higer resistence durability with downy mildew infection approximately 13,59 % - 20,39 % in vulnerability comparison (Anoman) reached 100%. The systemic influence of the characteristic of resistance durability also appeared on the production variable and weight of 1000 seeds.Â